Viral churches : helping church planters become movement makers - Stetzer, Ed.; Bird, Warren (San Francisco : Jossey-Bass, 2010)
Based on a study that was commissioned by the Leadership Network, this book reveals the best practices in church planting and uncovers the common threads among them. --from publisher description.
Church planting : the new evangelism -- Growth by addition : big contrast to multiplication -- New players : aggressive local churches and church planting networks -- Kingdom cooperation : church planters learning together -- Predictors of success : recruitment, assessment, and deployment -- Thriving : new church survival rates -- House churches : separating reality from fiction -- Multisite strategy : a fast-growing trend that affects planting -- Rapid growth : still not reproduction -- Funding : partnerships matter -- The new scorecard : measuring a church multiplication movement -- Obstacles to missional replication : what holds us back -- Solving the toughest challenges.
Includes bibliographical references (pages 215-232) and index.
Keywords: Church development, New